Safety and Efficacy of an Innovative Airway Clearance Device Versus Manual Chest Physiotherapy Techniques For Airway Secretion Clearance: a Feasibility Study. Issue 1 (June 2020) - , Philippe Giovannetti; Morin, Laurent; Reynaud-Gaubert, Martine
No abstract available